Caracterização bioquímica e molecular de Cryptococcus spp. isolados de excretas ambientais de pombos (Columba livia domestica) - Colombo, G. [UNESP]; Táparo, C. V. [UNESP]; Araújo, E. C. [UNESP]; Makatu, M. Y. [UNESP]; Santos, F. S. [UNESP]; Marinho, M. [UNESP] (FapUNIFESP (SciELO), 2015)
Pigeons have a rich diversity of microrganisms, including fungi saprobes such as the genus Cryptococcus that can act as a pathogen for humans and animals. The aim of this was their isolation, biochemical and molecular characterization of samples of Cryptococcus from ambientas avian excreta. One hundred environmental samples,representative of the area equidistant from Araçatuba, São Paulo points were collected. The samples were removed and stored in collection bottles, sent to the Laboratory of Bacteriology and Mycology of FMVA, where they were processed and cultivated in duplicate on Petri dishes containing Sabouraud dextrose 4% and Niger and incubated at room temperature 30° C, respectively, for a period of no less than 15 days. Colonies after daily observation which were suggestive for yeast growth were re-isolated in Niger agar and subjected to biochemical analisis for further molecular characterization by PCR tests. As results, the biochemical and molecular characterization of 32 yeast colonies revealed 8% of cultures positive for Cryptococcus neoformans var. neoformans, 17% Rhodotorula rubidae and 7% Candida albicans. It was concluded that environmental avian excreta are active sites for replication of Cryptococcus neoformans var. neoformans and other yeasts with pathogenic potential. These constitute a public health risk, and preventive measures are necessary, such as cleaning and complete removal of excreta in order to minimize the risk of environmental exposure.
Biochemical and molecular characterization of Cryptococcus spp. isolates from environmental feces of pigeons (Columba livia domestic)
Keywords: Biochemist; Cryptococcus sp; PCR; Pigeons; Public health